Liquid-phase oxidation of alkanes with molecular oxygen catalyzed by high valent iron-based perovskite. Issue 50 (23rd April 2018) - Shibata, Satomi; Sugahara, Kosei; Kamata, Keigo; Hara, Michikazu
Abstract : A hexagonal BaFeO3− δ perovskite catalyst containing high valent iron species exhibits high catalytic performance for the aerobic oxidation of alkanes without the need for additives. Abstract : Hexagonal BaFeO3− δ containing high valent iron species acted as an efficient heterogeneous catalyst for the aerobic oxidation of alkanes without the need for additives. The activity of BaFeO3− δ was much higher than that of typical Fe 3+ /Fe 2+ -containing iron oxide-based catalysts, and the recovered catalyst could be reused without significant loss of catalytic performance.